Digital Rights and Criminal Law Reform in Indonesia: Addressing Surveillance, Data Protection, and Cybercrime Governance - Amran Amran; Muh. Tahir (Journal of Progressive Law and Legal Studies, 2026)
The rapid digitalization of contemporary societies has intensified tensions between criminal law enforcement and the protection of digital rights, particularly in emerging democracies. This study examines the structural challenges of safeguarding digital rights within Indonesia’s criminal law framework and identifies necessary reform pathways. Using a qualitative normative doctrinal approach structured as a single-country case study, the research analyses key statutory instruments, including the Electronic Information and Transactions Law and the 2022 Personal Data Protection Law, alongside relevant legal doctrines and comparative regulatory models. The findings reveal five interrelated structural constraints: regulatory lag, tension between criminalization and fundamental rights, doctrinal rigidity, evidentiary and enforcement limitations, and institutional as well as digital literacy deficits. The study identifies a normative asymmetry in which speech-related criminal enforcement has evolved more assertively than privacy protection mechanisms. It argues that Indonesia represents a hybrid statutory model of digital governance, distinct from the European constitutionalized regulatory approach and the United States’ intermediary-immunity paradigm. Effective reform requires harmonized legislation, proportional criminalization, institutional modernization, and rights-oriented judicial interpretation. By reconceptualizing digital rights protection as a structural transformation of criminal law, this study expands digital governance theory beyond Euro-American binaries and highlights the distinctive regulatory pathways of Global South democracies.